YopN and TyeA Hydrophobic Contacts Required for Regulating Ysc-Yop Type III Secretion Activity by Yersinia pseudotuberculosis - Amer, Ayad A. A.; Gurung, Jyoti M.; Costa, Tiago R. D.; Ruuth, Kristina; Zavialov, Anton V.; Forsberg, Åke; Francis, Matthew S. (Frontiers in Cellular and Infection Microbiology, 2016)
Yersinia bacteria target Yop effector toxins to the interior of host immune cells by the Ysc-Yop type III secretion system. A YopN-TyeA heterodimer is central to controlling Ysc-Yop targeting activity. A +1 frameshift event in the 3-prime end of yopN can also produce a singular secreted YopN-TyeA polypeptide that retains some regulatory function even though the C-terminal coding sequence of this YopN differs greatly from wild type. Thus, this YopN C-terminal segment was analysed for its role in type III secretion control. Bacteria producing YopN truncated after residue 278, or with altered sequence between residues 279 to 287, had lost type III secretion control and function. In contrast, YopN variants with manipulated sequence beyond residue 287 maintained full control and function. Scrutiny of the YopN-TyeA complex structure revealed that residue W279 functioned as a likely hydrophobic contact site with TyeA. Indeed, a YopNW279G mutant lost all ability to bind TyeA. The TyeA residue F8 was also critical for reciprocal YopN binding. Thus, we conclude that specific hydrophobic contacts between opposing YopN and TyeA termini establishes a complex needed for regulating Ysc-Yop activity.